IMOBILISASI ENZIM LIPASE PADA SILIKA GEL SEBAGAI BIOKATALIS UNTUK REAKSI HIDROLISIS MINYAK KELAPA SAWIT - , FENDI YOGA WARDANA; , Deni Pranowo, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Immobilization of lipase enzyme on silica gel with encapsulation method has been performed. This study aims to improve reuse of lipase immobilized by silica gel, as well as the enzyme stability to the effects of temperature changes and pH in the hydrolysis reaction of palm oil. The immobilized lipase enzyme made by mixing a solution of lipase in phosphate buffer solution of silica sol gel at room temperature to form a solid gel which then allowed to stand for 24 hours. Percentage of silica encapsulated enzyme were analyzed by the biuret method using spectrophotometer UV-Vis. The catalytic activity and the ability to use repeatedly in the hydrolysis reaction of the immobilized lipase enzyme on silica gel has been tested, as well as its stability against temperature changes and pH of the hydrolysis reaction. The results showed that the percentage of lipase immobilized on silica gel is 64.024%, but after 5 washes, percentage of immobilized lipase only 28.041%. Activity of lipase immobilized silica gel is lower than the free lipase. However, the lipase enzyme immobilized by silica gel can be used up to 5 times in hydrolysis reaction with the highest reaction percentage of free fatty acid product is 17.407% and the lowest is 8.601%. Lipase immobilized silica gel is more stable against temperature changes and pH than free lipase enzymes, each enzyme has an optimum temperature at 35 Â°C and optimum pH 7.